Effect Methanol, Ethanol, Butanol on the Emissions Characteristics of Gasoline Engine - Syarifudin Syarifudin; Firman Lukman Sanjaya; Faqih Fatkhurrozak; M. Khumaidi Usman; Yohanes Sibagariang; Hasan KÃ¶ten (Automotive Experiences, 2021)
The increasing volume of motorized vehicles leads to an increase in dependence on fossil fuels and an increase in air pollution. The problem can be reduced by utilizing renewable alcohol fuels such as methanol, ethanol, and butanol. The high number of octane and oxygen content is the main reason. Therefore, this study aims to observe the exhaust emissions of the 160 cc gasoline engine with a mixture of methanol, ethanol, and butanol. The percentage of alcohol used is 0 % to 30 % by volume. The test was carried out in 2000, 3000, and 4000 rpm. The results of the study explained that the use of methanol, ethanol, butanol in the fuel mixture was proven to reduce exhaust emissions. CO and HC emissions decreased as the percentage of alcohol in the fuel increased. The highest reduction in CO and HC emission in methanol blended fuel was 30 %, 94.55 % and 82.71 %, respectively. Meanwhile, CO2 emissions increased by 34.88 % at 2000 rpm engine speed. Based on this test, the addition of methanol to fuel can reduce exhaust emissions better than ethanol and butanol.